How are tonoplast proteins degraded? - Maîtrejean, Marie (Landes Bioscience, 2011)
Protein turnover is fundamental both for development and cellular homeostasis. The mechanisms responsible for the turnover of integral membrane proteins in plant cells are however still largely unknown. Recently, considerable attention has been devoted to the degradation of plasma membrane proteins. We have now studied the turnover of a tonoplast protein, the potassium channel TPK1, in fully differentiated Arabidopsis leaf cells and showed that its degradation occurs upon internalization into the vacuole. Here, we discuss the possible mechanisms and triggering events involved.